Trypanocidals effectivity against some isolates of Trypanosoma evansi propagated in mice - Didik Tulus Subekti; I. Yuniarto; . Sulinawati; H. Susiani; F. Amaliah; B. Santosa (Jurnal Ilmu Ternak dan Veteriner, 2015)
Surra is one of infectious diseases in various types of animals caused by blood parasites called Trypanosoma evansi. It is fatally occurred, especially in horse, buffalo and camel. Surra may be controlled by effectively trypanocidals treatment based on the results of its sensitivity test. Therefore, it is necessary to study the effectiveness of various trypanocidal against some T.evansi isolates originating from several regions in Indonesia with surra case to determine its suitability and efficacy. The test was carried out by pre-test - post-test. Mice were infected by several T.evansi isolates from various infected areas. Their parasitaemia were observed. After reaching peak of parasitemia, the mice were treated by trypanocidal with different doses. Parasitaemia alteration was observed for one month. Observation results showed that all isolates had different sensitivity to the trypanocidals, so that trypanocidals application tended to specific location. Generally, suramin and melarsomine dihydrochloride were the most effective trypanocidal for some Indonesian isolates. In contrast, isometamidium chloride was not recommended to be used for surra control in Indonesia. Key Words: Trypanosoma evansi, Trypanocidal, Parasitemia, Surra